EEG phase synchronization in patients with paranoid schizophrenia - Bob, Petr; Palus, Milan; Susta, Marek; Glaslova, Katerina (Neuroscience letters, 2008)
Recent findings suggest that specific deficits in neural synchrony and binding may underlie cognitive disturbances in schizophrenia and that key aspects of schizophrenia pathology involve discoordination and disconnection of distributed processes in multiple cortical areas associated with cognitive deficits. In the present study we aimed to investigate the underlying cortical mechanism of disturbed frontal-temporal-central-parietal connectivity in schizophrenia by examination of the synchronization patterns using wavelet phase synchronization index and coherence between all defined couples of 8 EEG signals recorded at different cortical sites in its relationship to positive and negative symptoms of schizophrenia. 31 adult schizophrenic outpatients with diagnosis of paranoid schizophrenia (mean age 27.4) were assessed in the study. The obtained results present the first quantitative evidence indicating direct relationship between wavelet phase synchronization and coherence in pairs of EEG signals recorded from frontal, temporal, central and parietal brain areas and positive and negative symptoms of schizophrenia. The performed analysis demonstrates that the level of phase synchronization and coherence in some pairs of EEG signals is inversely related to positive symptoms, negative symptoms and general psychopathology in temporal scales (frequency ranges) given by wavelet frequencies (WFs) equal to or higher than 7.56 Hz, and positively related to negative symptoms in wavelet frequencies equal to or lower than 5.35 Hz. This finding suggests that higher and lower frequencies may play a specific role in binding and connectivity and may be related to decreased or increased synchrony with specific manifestation in cognitive deficits of schizophrenia.
Keywords: Cortical Synchronization; dospělí; korová synchronizace; Female; Brain Mapping; Adult; mladý dospělý; ženské pohlaví; paranoidní schizofrenie; lidé; mapování mozku; neparametrická statistika; Male; Young Adult; mozková kůra; Cerebral Cortex; Statistics, Nonparametric; mužské pohlaví; Schizophrenia, Paranoid; elektroencefalografie; Electroencephalography; Humans